Temporal variations of atmospheric greenhouse gases and their related gases at Syowa Station, Antarctica and Ny-Alesund, Svalbard. - Shinji Morimoto; Shigeyuki Ishidoya; Kentarou Ishijima; Hisashi Yashiro; Taku Umezawa; Gen Hashida; Satoshi Sugawara; Shuji Aoki; Takakiyo Nakazawa; Takashi Yamanouchi (National Institute of Polar Research, 2010)
To elucidate temporal variations of greenhouse gases and their related gases in the Arctic and Antarctic regions and to investigate their sources and sinks, systematic measurements of atmospheric CO_2, CH_4CO, N_2O, O_2 and tropospheric O_3 concentrations have been carried out at Syowa Station, Antarctica and Ny-Alesund, Svalbard. The CO_2 concentrations at both polar sites have increased at a rate of about 1.9 ppmv yr^, reflecting fossil fuel combustion and land use change. The CH_4 concentrations also showed clear seasonal cycles superimposed on complex secular trends. The increase rate of the CH_4 concentration varied with time. CH_4 increases were observed until 1999, the concentrations remained steady from 2000 to 2006 and then rapid increases were observed in 2007. Stable isotope data of CH_4 revealed causes of the seasonal cycles and the secular variations of the CH_4 concentrations. The O_2 concentrations (δ(O_2 N_2)) at both polar sites showed prominent seasonal cycles and secular decreasing trends. From analyses of the Atmospheric Potential Oxygen (APO) and CO_2 concentrations, the CO_2 uptake rates by the terrestrial biosphere and the ocean were estimated to be 1.1 and 2.7 GtC yr^, respectively. By comparing the N_2O concentrations observed at Ny-Alesund and numerical model results, it was suggested that the observed seasonal N_2O cycle could be enlarged by intrusion of a stratospheric air mass with low N_2O concentration into the troposphere in summer. With an analysis using a three dimensional chemical-transport model and the CO concentration at Syowa Station, sporadic increases of CO concentration observed in February-March, 2003 and February, 2007 were ascribed to CO release by large-scale forest fires in Australia. Surface ozone depletion events were observed more than 40 times at Syowa Station from 1988 to 2007.